2013
DOI: 10.1126/science.1233213
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution of Multiple Traits Through Multiple Mutations at a Single Gene

Abstract: The identification of precise mutations is required for a complete understanding of the underlying molecular and evolutionary mechanisms driving adaptive phenotypic change. Using plasticine models in the field, we show that the light coat color of deer mice that recently colonized the light-colored soil of the Nebraska Sand Hills provides a strong selective advantage against visually hunting predators. Color variation in an admixed population suggests that this light Sand Hills phenotype is composed of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
356
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(377 citation statements)
references
References 44 publications
(22 reference statements)
17
356
0
1
Order By: Relevance
“…One such example is the evolution of cryptic colouration in wild populations of deer mice 23 . In the Nebraska Sand Hills population, population genetic and functional evidence has been found for positive selection acting on a small number of mutations modifying different aspects of the cryptic phenotype, all contained within the Agouti gene region 24 . Three lines of population genetic evidence suggest that selection began acting on these mutations when they arose (that is, selection on a de novo mutation): (1) the beneficial mutations appear to be carried on single haplotypes (though, as discussed above, selection on standing variation may indeed often only result in a single haplotype fixation), (2) the beneficial mutations have not been sampled off of the Sand Hills region (that is, the mutation is unlikely to have been segregating at appreciable frequency in the ancestral population before the formation of the Sand Hills) and (3) using an approximate Bayesian approach, the age of the selected mutation has been inferred to be younger than the geological age of the Sand Hills 23 .…”
Section: Nature Communications | Doi: 101038/ncomms6281mentioning
confidence: 99%
See 1 more Smart Citation
“…One such example is the evolution of cryptic colouration in wild populations of deer mice 23 . In the Nebraska Sand Hills population, population genetic and functional evidence has been found for positive selection acting on a small number of mutations modifying different aspects of the cryptic phenotype, all contained within the Agouti gene region 24 . Three lines of population genetic evidence suggest that selection began acting on these mutations when they arose (that is, selection on a de novo mutation): (1) the beneficial mutations appear to be carried on single haplotypes (though, as discussed above, selection on standing variation may indeed often only result in a single haplotype fixation), (2) the beneficial mutations have not been sampled off of the Sand Hills region (that is, the mutation is unlikely to have been segregating at appreciable frequency in the ancestral population before the formation of the Sand Hills) and (3) using an approximate Bayesian approach, the age of the selected mutation has been inferred to be younger than the geological age of the Sand Hills 23 .…”
Section: Nature Communications | Doi: 101038/ncomms6281mentioning
confidence: 99%
“…In addition, ecological information pertaining to this phenotype exists as well. Performing a predation experiment with clay models, Linnen et al 24 demonstrated a strong selective advantage of crypsiswith conspicuous models being subject to avian predation significantly more than cryptic models. This result suggests that if the beneficial phenotype currently present in the Sand Hills was indeed present in the ancestral population, it was likely to be strongly deleterious.…”
Section: Nature Communications | Doi: 101038/ncomms6281mentioning
confidence: 99%
“…At one extreme, adaptation by independent populations to similar environments could be driven by the same frequency changes in the same alleles (and nucleotides) at the same loci, with the relevant alleles at each locus having arisen only once (that is, identical by descent). Moving away from this extreme, the same allele might have had multiple origins, the alleles might be different but have similar effects, the alleles might be different and have different effects, and different genes might be involved in the different populations (Arendt and Reznick, 2008;Manceau et al, 2010;Linnen et al, 2013).…”
Section: Ecosystem Functionmentioning
confidence: 99%
“…Prey that hide from predators by matching their backgrounds are termed cryptic (Edmunds 1974, Endler 1988, Stevens & Merilaita 2009). Thus, it is not surprising that cryptic organisms can be seen to vary in appearance over their distributions in ways that help them hide from predators (Kettlewell 1961, Forsman & Shine 1995, Cook et al 2012, Linnen et al 2013). However, some organisms are protected by defenses that make them unprofitable and advertise their unprofitability to predators with conspicuous warning signals.…”
Section: Geographic Variation For Different Preymentioning
confidence: 99%